Trailing spouse : estudo sobre a vivência da cônjuge do executivo expatriado - Souza, Adriana Alvarenga Madia de (2009)
Annually the number of executives that are sent with their spouses or families in an international relocation is growing. The studies try, once knowing the key variables involved in the adjustment process, to make the companies get higher levels of success in expatriations. The trailing spouses, as they are known, deeply feel the expatriation demands on their careers and on their couple relations. The present study look at the many challenges and problems faced, by these individuals, that leave their families, friends and normally, even their careers. The three case studies show that the personal resources specially the personality traits, the social abilities, and the will and determination are the strongest predictors of a good adjustment. The analysis of the relates shows that the marital resources, as free communication between the members of the couple, the concern about the other s feelings and the good time spent together are also strong indicators of a good adjustment, especially in distant cultures